$\begin{array}{1 1}(A)\;\text{True}\\(B)\;\text{False}\end{array} $

- $P(A \cup B)=P(A)+P(B)-P(A \cap B)$

Step 1:

Let us consider that

Probability of a person visiting a zoo and will see a giraffee=P(A)

Probability of a person visiting a zoo and will see a bear=P(B)

Probability of a person visiting both =P$(A\cup B)$

$P(A \cup B)=P(A)+P(B)-P(A \cap B)$

$0.52=0.72+0.84-P(A \cap B)$

Step 2:

$\therefore P(A \cap B)=0.72+0.84-0.52$

$\Rightarrow P(A \cap B)=1.04$

But $P(A \cup B)$ cannot be lesser than $P(A \cap B)$

$\therefore$ The given statement is False.

Ask Question

Tag:MathPhyChemBioOther

Take Test

...